2012
DOI: 10.5897/jece11.076
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals accumulation and distribution pattern in different vegetable crops

Abstract: Different vegetable crops grown on heavy metal contaminated soil showed marked difference in metal accumulation, their uptake and distribution pattern. Crop species also showed remarkable difference in metal concentration of various plant parts. Based on metal accumulation in edible parts and whole plants, root vegetables namely, radish and carrot registered lower accumulation of almost all heavy metals except Zn in radish root. However, leafy vegetables namely, spinach, amaranthus, mustard and fenugreek recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
43
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 13 publications
11
43
2
1
Order By: Relevance
“…The concentration of heavy metals present in the order of Fe>Zn>Mn>Cu>Ni>Pb>Cr. Singh [16] showed that irrespective of crop the average metal content was in the order of Zn>Cu>Pb>Ni>Cd. The transfer factor for amaranthus species is in the order of Zn>Mn>Fe>Cu>Ni>Pb>Cr as shown in figure 2.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The concentration of heavy metals present in the order of Fe>Zn>Mn>Cu>Ni>Pb>Cr. Singh [16] showed that irrespective of crop the average metal content was in the order of Zn>Cu>Pb>Ni>Cd. The transfer factor for amaranthus species is in the order of Zn>Mn>Fe>Cu>Ni>Pb>Cr as shown in figure 2.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Such suspended particles might precipitate at high concentrations in soils near highway and, to a lower extent, at lower concentrations away from the highway. There are several forms of heavy metals in soils, a soluble form which is available to be absorbed by plants as well as complexed forms consist of heavy metals combined with organic or in organic compounds (Singh et al, 2012 andRadulescu et al, 2013). Heavy metals translocation from soil solution through roots to other plant parts and accumulate in high concentrations causing a serious risk on human health when these plants are consumed (Ashworth and Alloway, 2004).…”
mentioning
confidence: 99%
“…미국EPA (Environmental Protection Agency)는 토양-작물-인체로 의 중금속 전이를 고려하여 토양 중 중금속 기준(SSLs, Screening Levels)을 설정할 필요가 있고, 이를 위해서 식용 작물의 생물농축계수(bioconcentration factor)를 적용할 것 을 추천하고 있다 (USEPA, 1996). 또한 국외연구 사례에서는 오염농경지에서 생산되는 농산물의 안전성확보를 위해 재배 가능한 작물의 우선순위를 제시하고 있기도 하다 (Singh et al, 2012). 반면 우리나라는 토양의 중금속 오염도 및 작물별 중금속 흡수율 차이를 고려하지 않고 관행작물을 지속적으로 재배하고 있다.…”
Section: 재배환경에서의 관리방안을 마련하기 위해서는 작물이 토 양으로부터 흡수한 중금속을 지상부로 전이시키는 양상 unclassified